Difficulties of fathers whose families evacuated voluntarily after the Fukushima nuclear disaster - Yoshioka‐Maeda, Kyoko; Kuroda, Mariko; Togari, Taisuke (Nursing & health sciences, 2018)
The Fukushima nuclear disaster in 2011 resulted in radiation exposure, and many evacuees felt anxious of its health risks. However, little is known about the difficulties faced by fathers whose families evacuated voluntarily. Therefore, the aim of the present case study was to clarify the difficulties and concerns of fathers whose families evacuated voluntarily after the Fukushima nuclear disaster. Eleven fathers in Fukushima were interviewed between 14 December 2014 and 25 February 2015. Four themes emerged: (i) seeking a safe place away from radiation exposure; (ii) burdens of a double life; (iii) feelings of isolation and perceived deterioration of health; and (iv) deciding on whether to continue voluntary evacuation. Fathers were anxious about radiation exposure, similar to mothers, and faced work–family conflicts from the voluntary evacuation of their families, including financial, physical, and mental sacrifice. Half of the fathers did not express their difficulties to others. Our findings identified a new type of conflict between people of a community who did/did not choose voluntary evacuation. Occupational health nurses should understand fathers’ feelings of isolation and monitor their health to prevent the development of stress‐related diseases.